Subdural Hygroma in an Infant with Marfan's Syndrome - Ballmann, Lisa; Scholl-Bürgi, Sabine; Karall, Thomas; Odri Komazec, Irena; Karall, Daniela; Michel, Miriam (Neuropediatrics, 2021)
Based on a patient encounter in which genetically confirmed Marfan's syndrome (MFS) underlay a spontaneously resolving subdural hygroma (SDHy) diagnosed in infancy, we review the literature of MFS clinically manifest in early life (early-onset MFS [EOMFS]) and of differential diagnoses of SDHy and subdural hemorrhage (SDHe) at this age. We found that rare instances of SDHy in the infant are associated with EOMFS. The most likely triggers are minimal trauma in daily life or spontaneous intracranial hypotension. The differential diagnosis of etiologies of SDHy include abusive and nonabusive head trauma, followed by perinatal events and infections. Incidental SDHy and benign enlargement of the subarachnoid spaces must further be kept in mind. SDHy exceptionally also may accompany orphan diseases. Thus, in the infant, EOMFS should be considered as a cause of SDHe and/or SDHy. Even in the absence of congestive heart failure, the combination of respiratory distress syndrome, muscular hypotonia, and joint hyperflexibility signals EOMFS. If EOMFS is suspected, monitoring is indicated for development of SDHe and SDHy with or without macrocephaly. Close follow-up is mandatory.
Keywords: child abuse; infant; Marfan's syndrome; neonate; subdural hemorrhage; subdural hygroma